Bullying in Schools: A Literature Review about Behavior Patterns, Causal Factors, and Their Impact on Students - Laila Sari (Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2026)
This study aims to comprehensively examine the phenomenon of bullying in schools by examining behavioral patterns, causal factors, and their impact on students. The focus of the research is directed at understanding the development of forms of bullying in educational environments and trends in academic studies over the past decade. The method used is qualitative research with a library research approach. Data were obtained from scientific articles indexed by Google Scholar and Dimensions with a publication period of 2015–2025 to ensure the data remains relevant and up-to-date. Furthermore, bibliometric analysis using VOSviewer was used to map research developments, the distribution of study areas, and the interconnectedness of themes in the school bullying literature. The results show that academic attention to bullying has increased significantly since 2020 in line with awareness of the importance of a safe educational environment. Verbal bullying is the most dominant form, followed by physical bullying, social bullying, and cyberbullying, which has grown rapidly due to advances in digital technology. The main contributing factors include weak parental supervision, peer influence, individual character, a less conducive school environment, media exposure, and unequal power relations reinforced by patriarchal and feudal cultures. The impact of bullying is complex, including anxiety, depression, low self-confidence, decreased academic achievement, and an increased risk of self-harm. Bibliometric mapping also shows that bullying research in Indonesia is still concentrated in West Java, Central Java, East Java, South Sulawesi, and North Sumatra only.